Cultural competence among nursing students and nurses working in acute care settings: a cross-sectional study - Selvedina Osmancevic; Franziska Großschädl; Christa Lohrmann (BMC, 2023)
Abstract Background The increasing cultural diversity in healthcare in European countries, including Austria, has highlighted the need to enhance nurses' cultural competence. Assessing cultural competence and identifying relevant influencing factors can help to improve culturally competent care. The aim of this study was to assess the cultural competence of nurses and nursing students working in Austrian acute care settings and to identify influencing factors using the Cultural Competence Assessment scale. Methods A cross-sectional design was used. Data collection was carried out in March 2021 with nurses and nursing students in the last year of their studies who were working in Austrian acute care settings. Descriptive analysis was applied to display the general characteristics of the study participants and the levels of their overall cultural competence. A multiple linear regression analysis was conducted to analyze the influencing factors of cultural competence. Results The nurses' cultural competence level was moderate to high (mean = 3.89; SD = .48). Their age, educational level, cultural diversity training and self-perceived cultural competence significantly influenced the level (F (6, 875) = 18.971, p < .0000, adj. R2 = 1.09). Conclusions Providing culturally competent healthcare services for culturally diverse patients is essential for all healthcare professionals, and especially for nurses who spend the most time with patients. Effective interventions, such as educational training, need to be implemented in order to deliver culturally competent care and potentially reduce disparities in healthcare and improve patient outcomes.